GC-MS Profiling and Bioactivities of Essential Oil and Extracts of Cinnamomum tamala (Buch.-Ham.) Nees & Eberm. Leaves from Kathmandu Valley, Nepal - Tandukar, Pooja; Das, Nabin; Pathak, Ishwor; Gautam, Daman Raj (Amrit Research Journal, 2022)
The present work reports the phytoconstituents present in the essential oil and four different solvent extracts of Cinnamomum tamala leaves. Their antibacterial, antifungal, and antioxidant potential were also evaluated. The extraction of essential oil was performed by hydro-distillation using Clevenger apparatus and its chemical composition was identified by gas chromatography coupled with mass spectrometry (GC-MS). The leaf extracts were obtained by the cold percolation method. Linalool and cinnamaldehyde (E) were major compounds in the oil. Phytochemical screening of the extracts revealed the presence of terpenoid, glycoside, tannin, reducing sugar, polyphenol, saponin, flavonoid, and alkaloid. Total phenolic content (TPC) and total flavonoid content (TFC) were quantified using Folin-Ciocalteu and Aluminium chloride colorimetric assay, respectively. The methanol extract (98.36 mg GAE/g) and ethyl acetate extract (90.44 mg GAE/g) showed higher TPC values. Similarly, the TFC value of ethyl acetate extract was higher (478.78 mg QE/ g) than the other extracts. The antioxidant activity of extracts was assessed by using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay in which the ethyl acetate extract showed high antioxidant efficacy. The essential oil and chloroform extract showed antifungal activity against Candida albicans, while only the oil showed activity against Shigella dysenteriae.